Aurora kinase A has a significant role as a therapeutic target and clinical biomarker in endometrial cancer - UMENE, KIYOKO (Int J Oncol, 2015)
Aurora kinase A (AURKA) regulates the cell cycle checkpoint and maintains genomic integrity. AURKA is overexpressed in various malignant tumors and its upregulation induces chromosomal instability, which leads to aneuploidy and cell transformation. To investigate the role of AURKA in endometrial cancer, we evaluated the association of immunohistochemical expression of AURKA with clinicopathological factors. Furthermore, we examined the effects of AURKA inhibition by transfected siRNA in HEC-1B cells on colony-forming ability, invasion and migration capacity, and chemosensitivity. Immunohistochemical staining showed that overexpression of AURKA was significantly associated with tumor grade (P<0.05) and poor histologic differentiation (P<0.05). The recurrence rate also tended to be high in cases with overexpression of AURKA (P<0.1) and these cases also had a tendency for shorter disease-free survival (DFS) (P<0.1). AURKA inhibition in endometrial cancer cell lines significantly decreased cell growth, invasion and migration (P<0.05), and increased chemosensitivity to paclitaxel. We also evaluated the efficacy of a combination of AURKA siRNA and paclitaxel against subcutaneous tumors formed in a nude mouse. After treatment, the tumor volume shrank significantly compared to treatment with paclitaxel only (P<0.05). To our knowledge, this is the first study in endometrial carcinoma to show a correlation between overexpression of AURKA and tumor grade, histological type and sensitivity to paclitaxel. AURKA is a promising therapeutic target in endometrial cancer and the combination therapy with AURKA inhibitors and paclitaxel could be effective for endometrial cancer that is resistant to conventional treatment and has a poor prognosis.